2018
DOI: 10.1093/rheumatology/key231
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions and their association with 2 year functional status and change in patients with hand osteoarthritis

Abstract: Illness perceptions seemed to be implicated in disability and its progression. Our results suggest that interventions could focus on improving baseline disability, potentially using illness perceptions to accomplish this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The mental health screening tool explained a substantial part of the variance in pain and hand function at baseline and 3 months. This highlights, in line with other studies [3-5, 8, 9, 12, 14-16, 18, 19, 25, 28, 30, 31, 33, 35, 36], the importance of mental health and its relation to treatment decisions and outcomes. The models with only the screening tool items performed nearly as well as the models using the full mental health measures (that is, the entire PCS, PHQ-4, and B-IPQ), which further substantiates the validity of our tool.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mental health screening tool explained a substantial part of the variance in pain and hand function at baseline and 3 months. This highlights, in line with other studies [3-5, 8, 9, 12, 14-16, 18, 19, 25, 28, 30, 31, 33, 35, 36], the importance of mental health and its relation to treatment decisions and outcomes. The models with only the screening tool items performed nearly as well as the models using the full mental health measures (that is, the entire PCS, PHQ-4, and B-IPQ), which further substantiates the validity of our tool.…”
Section: Discussionsupporting
confidence: 90%
“…In musculoskeletal healthcare, patient mental health has gained attention in recent years. Numerous studies have demonstrated that mental health factors influence symptoms, outcomes, and treatment choices [3-5, 8, 9, 12, 14-16, 18, 19, 25, 28, 30, 31, 33, 35, 36]. For example, patients with thumb-base osteoarthritis scheduled for surgery have worse psychologic profiles than their nonsurgical counterparts [37], suggesting that domains of mental health play an important role in choosing between surgical and nonsurgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Patient reported outcome measures (PROMs) generally play a key role when assessing arthritic conditions such as pain [15], physical disability [16], psychiatric disturbance [17], aesthetic problems [18,19] and poor health-related quality of life [12,13]. While a growing number of instruments are available and cover a wide range of the health sciences, we must use those most appropriate to the clinical setting [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Patient reported outcome measures (PROMs) generally play a key role when assessing arthritic conditions such as pain [15], physical dysfunction [16], psychiatric disturbance [17], aesthetic problems [18,19] and poor health-related quality of life [12,13]. While a growing number of instruments are available and cover a wide range of the health sciences, we must use those most appropriate to the clinical setting [20,21].…”
Section: Introductionmentioning
confidence: 99%